Integration of hierarchical tin Sulfide@Sulfur-Doped carbon porous composites with enhanced performance for triiodide reduction. (August 2022) - Liu, Zuhui; Xin, Wen; Xie, Wenrui; Wang, Xiuwen; Li, Ning; Yuan, Zanxiang; Li, Yanzi; Wang, Jianxin
Abstract: Constructing composites with positively synergistic effect is deemed as an effective strategy to further improve photovoltaic performance of dye-sensitized solar cells (DSSCs). However, the controllable synthesis of composites with intimate interface is still a big challenge. In this work, the solvothermal synthesis using SnCl2 and SnSO4 as tin source allows to grow the SnS microspheres (cSnS) and irregular SnS (sSnS). Subsequently, the hierarchical tin sulfide@sulfur-doped carbon porous composites (SnS@SC) have been ingenious synthesized by using SnCl2 as tin source through a facile hydrothermal method followed by the pyrolysis of coated glucose containing sulfur species under the nitridation atmosphere. As expected, the as-designed SnS@SC exhibited outstanding catalytic activity for triiodide reduction reaction (IRR) accompanying with a photoelectric conversion efficiency (PCE) of 7.54%, which reaches as high as 98.7% to that of the Pt (7.64%), as well as higher than that of the cSnS (6.21%) and sSnS (5.20%) in parallel. Compared with cSnS and sSnS, the further enhanced performance of SnS@SC can be mainly attributed to the more exposed active sites, the effective permeation of electrolyte, the decreased resistance, intimate interface and synergistic effect between SnS and S-doped carbon. Our discovery provides an extensible pathway to develop the active-site-enriched composites with beneficial structures in the field of the energy conversion. Graphical abstract: Image 1 Highlights: cSnS and sSnS were prepared by using SnCl2 and SnSO4 as tin source. Hierarchical SnS@SC porous composites were ingenious synthesized. Performance can be further improved by converting cSnS to SnS@SC. A PCE of 7.54% was achieved in SnS@SC-based DSSCs, which reaches as high as 98.7% to that of Pt control-device (7.64%).